On the experimental characterisation of crack tip displacement fields on nonplanar elements: Numerical and experimental analysis. (April 2023) - Camacho-Reyes, A.; Antunes, F.V.; Vasco-Olmo, J.M.; Diaz, F.A.; Felipe-Sesé, L.A.
Highlights: Characterisation of crack tip fields in non-planar cracked elements. Image Decomposition technique applied to compare FEA and DIC crack tip data. High accuracy approach for SIFs determination on non-flat cracked surfaces. Abstract: In this work, a numerical and experimental study about crack tip fields characterisation on curve-cracked elements has been performed. This study combines a novel differential geometry approach combined with 3D-DIC and FEA results to determine crack-tip parameters from the displacement field on a curved cracked element. The work aims to validate and compare some aspects that cannot be addressed using 3D-DIC. SIFs for different crack lengths are determined using DIC and FEA data and compared In addition, a comprehensive comparison between experimental and numerical fields is done using an Image Decomposition technique based on Tchebichef polynomials.